Students' 'Uses and Gratification Expectancy' conceptual framework in relation to e-learning resources - Mondi, Makingu; Woods, Peter; Rafi, Ahmad (INST ASIA PACIFIC EDUCATION DEVELOPMENT, 2007)
This paper presents the systematic development of a 'Uses and Gratification Expectancy' (UGE) conceptual framework which is able to predict students' 'Perceived e-Learning Experience.' It is argued that students' UGE as regards e-learning resources cannot be implicitly or explicitly explored without first examining underlying communication theories and learning perspectives. As such, the theoretical framework is grounded in the confluence of theories from communication theories and learning perspectives. The integration of Expectancy-value Theory, and the Uses and Gratification Theory serves to accommodate the suggestion that e-learning resources offer gratifications that are expected and valued by students. The key theoretical and practical assumptions of the UGE approach are highlighted and consistently implemented in the conceptual edifice.